2008
DOI: 10.1002/chp.161
|View full text |Cite
|
Sign up to set email alerts
|

Distance education for physicians: Adaptation of a Canadian experience to Uruguay

Abstract: The key aspects of transforming this course from one country to another with different resources, health care systems, culture, and language are analyzed. Problems encountered are described, as well as their possible solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
8
0
3
Order By: Relevance
“…Commitments to change have been advocated to both stimulate and assess the effectiveness of continuing education interventions. 11,12 In this activity, physicians' commitments demonstrate willingness to adopt good practices and evidence-based skills regarding tobacco cessation, and showed good correlation with the course objectives stated initially though few completed follow-up. Loss to follow-up for the CTC component is another limitation in this course evaluation; the number of physicians who completed follow-up was too small to allow further statistical analysis between groups and increases the possibility of selection bias.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Commitments to change have been advocated to both stimulate and assess the effectiveness of continuing education interventions. 11,12 In this activity, physicians' commitments demonstrate willingness to adopt good practices and evidence-based skills regarding tobacco cessation, and showed good correlation with the course objectives stated initially though few completed follow-up. Loss to follow-up for the CTC component is another limitation in this course evaluation; the number of physicians who completed follow-up was too small to allow further statistical analysis between groups and increases the possibility of selection bias.…”
Section: Discussionmentioning
confidence: 83%
“…Other possible barriers to online education include technical difficulties and lack of computer skill as reported previously. 11,27 It will be important in future work to try to ensure and enhance participants' interaction, since studies have shown that better learning outcomes and satisfaction result from higher interaction and involvement. [28][29][30] The wiki offered physicians an opportunity to work together on a specific task related to tobacco control, such as setting specialized tobacco cessation services and community-based activities.…”
Section: Discussionmentioning
confidence: 98%
“…A oferta de cursos na área da saúde a localidades diversas enfrenta o desafio da diversidade cultural e, em alguns casos, diferenças nos sistemas de saúde 14 . Disponibilidade de recursos diagnósticos e valores culturais, principalmente aqueles relacionados ao estilo de vida, podem influenciar diagnósticos e decisões terapêuticas.…”
Section: Discussionunclassified
“…Essas características devem ser observadas durante o planejamento de ações voltadas à formação de profissionais da área da saúde. Programas educacionais originalmente desenvolvidos para o público de uma região, muitas vezes não podem ser aplicados diretamente, mantendo a efetividade, a outros grupos sem que haja uma remodelação dos recursos didáticos, seja por questões técnicas, como conectividade a internet, seja por diferenças socioculturais ou epidemiológicas 14 . O processo de adaptação dos conteúdos vivenciado na UNA-SUS/UFCSPA também ocorreu em outros centros [14][15][16] .…”
Section: Discussionunclassified
See 1 more Smart Citation